A comparative study of quality of life with respect to EORTC scale in lung cancer patients undergoing chemo radiation - Tejale, Praghnya S.; Mahobia, Vijay K.; Diwan, Ashok K. (International Journal of Research in Medical Sciences, 2025)
Background: In lung cancer patient’s data regarding comparison of quality-of-life pre and post treatment as per EORTC score is sparse. So, we conducted this study on lung cancer patients to compare the quality of life. Methods: Demographic data were collected from new lung cancer patients (not taking treatment elsewhere) attending the Radiation and Oncology Department of Government Medical College, Nagpur. ECOG performance score noted before starting treatment. Pre-treatment and 6 weeks’ post-treatment quality of life score measured according to EORTC QLQ-C30 and EORTC QLQ-LC13 and compared. Treatment given was either chemotherapy, radiotherapy or chemo-radiotherapy according to standard guidelines. Results: 79 patients received treatment and completed regular follow-up. The mean age of the patients was 56.06 years (SD±10.46). The number of male patients was 47, and the number of female patients was 32. The number of patients with ECOG scores 0, 1, 2, 3, and 4 was 3 (3.8%), 35 (44.3%), 24 (30.4%), 14 (17.7%), and 3 (3.8%), respectively. EORTC QLQ-C30 score pre- and post-treatment was 70.14 (±16.309) and 53.58 (±16.445), respectively (p<0.001). Conclusions: QoL in lung cancer patients improves after chemotherapy, radiotherapy, or chemo-radiotherapy. EORTC is a simple and useful score system for comparing pre- and post-treatment QoL.